2002
DOI: 10.1007/s00436-002-0691-7
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural dominance and Taenia crassiceps parasitism in BALB/c male mice

Abstract: Behavioural dominance relationships in mouse populations are based upon fighting and antagonistic behaviour. Social rank is affected by the physiological states present in the mice. Experimental infection by Taenia crassiceps cysticerci induced physiological disorders and disrupted the dominant-subordinate status. Infected male mice showed strong perturbations in territorial behaviour and aggressiveness. Infected dominant male mice did not show a significant reversal of dominance order compared to uninfected m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Males that are more disease resistant may also be relatively good competitors and likely to achieve high status. The reverse could also hold; for example, Taenia crassiceps infection in male mice decreases the likelihood that a male will achieve high dominance status [128]. …”
Section: Discussionmentioning
confidence: 99%
“…Males that are more disease resistant may also be relatively good competitors and likely to achieve high status. The reverse could also hold; for example, Taenia crassiceps infection in male mice decreases the likelihood that a male will achieve high dominance status [128]. …”
Section: Discussionmentioning
confidence: 99%
“…This experimental setting is a fascinating example of the interactive host-parasite neuroimmunoendocrine network. It has been shown that hormonal changes in cysticercotic mice profoundly affect their behavior, including sexual activity [18], aggressiveness [37], social status and defense response [21]. Male mice infected with T. crassiceps show remarkable changes in sexual behavior characterized by a complete loss of the ejaculation response early in the infection (6 weeks), followed by a gradual decrease in the number of mounts and intromissions, as well as increasing in their latencies, until none of the parasitized mice showed any sexual response toward female mice [18].…”
Section: Discussionmentioning
confidence: 99%
“…In female mice, infection also causes perturbations in sexual behavior, characterized by a reduced receptivity to the male, as well disruption of the estrous cycle [20]. Regarding social behavior, infection disrupts the dominant-subordinate status [21]. Infected animals assume a subordinate status as compared with healthy ones [22].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of T. crassiceps in the mouse's body can lead to the modulation of the host's immune system [5]. It has been observed that infection with T. crassiceps can induce immune responses in the brains of mice, which may lead to inflammation and changes in brain function [6,7]. Research on T. crassiceps infection in mice has investigated its correlation with behavioral changes, indicating that the presence of the parasite might influence mouse behavior.…”
Section: Introductionmentioning
confidence: 99%